Evaluating organizational characteristics complementary with enterprise software products - Hovelja, Tomaž; Vasilecas, Olegas; Kalibatienė, Diana; Rupnik, Rok (Journal of Business Economics and Management, 2020)
Implementation, deployment and maintenance of enterprise software pre-configured products are one of the key challenges managers need to address in order to stay competitive in the never ending search to find better ways of conducting business. In the literature there are discovered two general approaches through which managers can use for a successful implementation, deployment and maintenance of enterprise software products. First approach is based on the internal re-deployment of the managerial practices that are already used to manage other fields in the enterprise. Second – the deployment of “world-wide” industry “best practices” that international vendors of enterprise software and their local representatives sell as part of their pre-configured software products. This paper presents a novel model that enables enterprises to systematically evaluate the fit between their specific organizational characteristics and the organizational characteristics complementary with successful deployment of international pre-configured enterprise software products. The proposed model is tested through a comparison of two groups of enter-prises from the population of 1000 biggest enterprises in Slovenia. The first group mostly invests in local, while the second group mostly invests in international enterprise software products. The paper finds that on average there are significant and relevant differences in 44% of the examined organizational characteristics between the groups of enterprises that mostly invest in international or local enterprise software products. The model serves as a comprehensive organizational risk checklist for enterprises that are about to invest in enterprise software products.